Constructing STR Multiplexes for Individual Identification of Hungarian Red Deer1. Issue 4 (11th February 2014) - Szabolcsi, Zoltan; Egyed, Balazs; Zenke, Petra; Padar, Zsolt; Borsy, Adrienn; Steger, Viktor; Pasztor, Erzsebet; Csanyi, Sandor; Buzas, Zsuzsanna; Orosz, Laszlo
Abstract Red deer is the most valuable game of the fauna in Hungary, and there is a strong need for genetic identification of individuals. For this purpose, 10 tetranucleotide STR markers were developed and amplified in two 5‐plex systems. The study presented here includes the flanking region sequence analysis and the allele nomenclature of the 10 loci as well as the PCR optimization of the DeerPlex I and II. LD pairwise tests and cross‐species similarity analyses showed the 10 loci to be independently inherited. Considerable levels of genetic differences between two subpopulations were recorded, and FST was 0.034 using AMOVA. The average probability of identity (PIave) was at the value of 2.6736 × 10−15. This low value for PIave nearly eliminates false identification. An illegal hunting case solved by DeerPlex is described herein. The calculated likelihood ratio (LR) illustrates the potential of the 10 red deer microsatellite markers for forensic investigations.